Identifikasi Aspergillus flavus pada Kue Pia yang Di Jual Di Dusun Warurejo Kabupaten Pasuruan: Identification of Aspergillus flavus on Pia Cakes Sold in Warurejo Hamlet, Pasuruan Regency - Lindawati, Sari; Rini, Chylen Setiyo (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Warurejo village that located in Pasuruan district is the center of pia cake business expecially green beans pia. Pia cake is a cake that can’t durable cause by microorganism that come from the less clear and wraping in production. It makes contamination of mycotoxins from spesies of the fungus is Aspergillus flavus. Aspergillus flavus can produce a toxin metabolite compund that is aflatoxin. If aflatoxin is continuous consumtion will cause liver cancer. This research aim to determine presence of Aspergillus flavus on pia cake that produce by center of pia cake business in Warurejo village. It will be research with storage time of 0, 5 and 10 days. This study is descriptive, the number of sample taken randomly as many as 30 samples from 33 stores. Research this is obtained by macroscopically and microscopically. In macroscopically colonis that, look yellowish greeen and on the bottom is yellow to brown while microscopically rounded vesicles and conidi are round. 73% of Aspergillus flavus has positive contaminated fungus in 0 days and 5 days. 97% positive was Aspergillus flavus with 10 days storage time. In day 10 found more Aspergillus flavus fungus that on days 0 and 5 days.